إعداد المواد التعليمية لمهارة القراءة في تعليم اللغة العربية لغير الناطقين بها بإندونيسيا ‏ - Nahdliyyatul Azimah (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2021)
This study was presented to prepare educational materials as an educational book to develop student's reading skills and experience among second-semester students in Class G, Faculty of Islamic Economics and Commerce, Islamic State University of Sunan Ampel Surabaya.As for the research methodology used, it is developmental research, and the researcher took the research steps presented by Sugiyono. Moreover, the researcher used the pre and post-test and published the questionnaire to the research group to know the effectiveness of the developed book.The results of the research indicated that the educational book